Synthesis and X-ray crystallography of nonanuclear cobalt cluster and mononuclear cobalt complex: Effect of phosphine on the formation of cobalt complexes. (15th November 2020) - Hamaguchi, Tomohiko; Ono, Daiji; Matsuda, Yutaro; Kawata, Satoshi
Graphical abstract: Nonanuclear complex [Co{Co4 (µ4 -O)(1-methylimidazole-2-thiolate)6 }2 ](BF4 )2 and mononuclear complex [Co(bis(1-methyl-imidazol-2-yl)disulfide)2 ](BF4 )2 were synthesized using almost the same method and characterized by X-ray diffraction study. Synthesis of the two complexes differed in the presence and absence of phosphine. The effect of phosphine on the formation of these complexes was discussed. Highlights: Nonanuclear and mononuclear cobalt complex were synthesized and characterized. The presence and absence of phosphine produced the Co9 and Co1 complex, respectively. Phosphine would affect the synthesis not as ligand but as oxygen scavenger. Abstract: Nonanuclear complex [Co{Co4 (µ4 -O)(1-methylimidazole-2-thiolate)6 }2 ](BF4 )2 and mononuclear complex [Co(bis(1-methyl-imidazol-2-yl)disulfide)2 ](BF4 )2 were synthesized using almost the same method and characterized by X-ray diffraction study. Although almost the same method was used during synthesis, the presence and absence of phosphine produced the nonanuclear complex and mononuclear complex, respectively. In addition, the mononuclear complex has bis(1-methyl-imidazol-2-yl)disulfide that can be obtained from the oxidation of 1-methylimidazole-2-thiolate ligand. Therefore, phosphine ligand could prevent the oxidation of 1-methylimidazole-2-thiolate ligand.